Dietary precursors and cardiovascular disease: A Mendelian randomization study - Jing, Wangwei; Huang, Shushi; Xiang, Pingping; Huang, Jiniu; Yu, Hong (Frontiers in Cardiovascular Medicine, 2023)
The Dietary precursor has been identified as a contributor in the development of cardiovascular disease. However, it is inconsistent if dietary precursors could affect the process of cardiovascular disease. Here we performed Mendelian randomization (MR) analysis of the data from genome-wide association study of European ancestry to evaluate the independent effects of three dietary precursors on cardiovascular disease (CVD), myocardial infarction (MI), heart failure (HF), atrial fibrillation (AF) and valvular disease (VHD). Inverse variance weighting method was used for the MR estimation. Sensitivity was determined by MR-PRESSO analysis, weighted median analysis, MR-Egger analysis, and Leave-one-out analysis. We found that elevated choline level had a causal relationship with VHD (odds ratio (OR)=1.087, 95% confidence interval (CI), 1.003-1.178, P =0.041) and MI (odds ratio (OR)=1.250, 95% confidence interval (CI), 1.041-1.501, P =0.017) by single-variable MR analysis. Furthermore, elevated carnitine level was associated with MI (odds ratio (OR)=5.007, 95% confidence interval (CI), 1.693-14.808, P =0.004) and HF (odds ratio (OR)=2.176, 95% confidence interval (CI), 1.252-3.780, P =0.006) risk. In addition, elevated phosphatidylcholine level can increase the risk of MI (odds ratio (OR)=1.197, 95% confidence interval (CI), 1.026-1.397, P =0.022). In conclusion, our data show that choline increases VHD or MI risk, carnitine increases the risk of MI or HF, and phosphatidylcholine increases HF risk. These findings suggest the possibility that decrease in choline level in circulation may be able to reduce overall VHD or MI risk, reduce in carnitine level could be decrease MI and HF risks as well as decrease in phosphatidylcholine could reduce MI risk.